Hedging Decisions and Its Affecting Factors on Mining Companies Listed in the Indonesian Sharia Stock Index (ISSI) - Rahayu, Sri; Zufrizal, Zufrizal; Astuty, Widia; Triastuti, Heny (Budapest International Research and Critics University, 2020)
International trade encourages increased competition as well as volatility in market prices, which causes uncertainty or increased business risk in maintaining business. The risk of fluctuations in foreign exchange rates is the biggest risk that affects international trading activities, so to reduce the impact of this risk a company needs to carry out risk management by carrying out hedging activities. This study aims to determine and explain the effect of leverage (Debt to Equity Ratio), liquidity (Current Ratio), firm size, and profitability (Return On Asset) on hedging decisions in companies listed on the Indonesian Sharia Stock Index (ISSI) for the period 2016- 2018. The sample selection in this study used a purposive sampling method and obtained a sample of 12 mining companies. The method of analysis used in this research is logistic regression method. Based on the research results, it shows that the Debt to Equity Ratio, Current Ratio, and firm size have an effect on hedging decisions, while Return on Assets has no effect on hedging decisions.